Spectral theory and Wiener-Itô decomposition for the image of a Jacobi field - Berezansky, Yu.M.; Pulemyotov, A.D. (Український математичний журнал, 2007)
Assume that K⁺ : H_ → T_ is a bounded operator, where H_ and T_ are Hilbert spaces and ρ is a measure
on the space H_. Denote by ρK the image of the measure ρ under K⁺. This paper aims to study the measure
ρK assuming ρ to be the spectral measure of a Jacobi field. We obtain a family of operators whose spectral
measure equals ρK. We also obtain an analogue of the Wiener – Ito decomposition for ˆ ρK. Finally, we illustrate
the results obtained by carrying out the explicit calculations for the case, where ρK is a Levy noise measure. Припустимо, що K⁺:H_→T_ є обмеженим оператором, де H_ та T_ – гільбертові простори, i p – міра на просторі H_. Позначимо через ρK зображення міри ρ під дією K⁺. Метою цієї роботи є вивчення міри ρK за припущення, що ρ є спектральною мірою поля Якобі. Отримано сім'ю операторів із спектральною мірою, рівною ρK, а також аналог розкладу Вінера – Іто для ρK. Одержані результати проілюстровано явними розрахунками для випадку, коли ρK є мірою шуму Леві.